An Innovative Scheme to Persuade Secure Data Uploading In Public Cloud - Fancy.C, Sowmiya.B, Ida Serphim.B, Dinesh.S (International Journal of Advanced Science and Technology, 2020)
In recent days people focus more on data storage on the public cloud servers (PCSs).Cloud storage means the storage of our personal data over remote servers which can be accessed by the use of the internet. The various cloud types include Public, Private, and Hybrid. The main demerit of public cloud is the weakness in security. That is why people prefer private cloud despite its disadvantages like high cost, and maintenance which is left to the user. We propose a solution to improve the security issues in the public cloud and attract more clients to use the public cloud. The proposed work focuses on allowing the clients to store information in the cloud, also making use of administrations which are given by different distributed storage suppliers. We propose a study on the achievable security justifies by making utilization of different unmistakable mists at the same time. The pseudo key generator helps in generating private keys during file access. Before key transmission, it is transformed into cipher text with the help of 3DES encryption algorithm. To give information privacy we propose a protected information stowing away and compression method in distributed storage. Our aim is to contribute through a combination of image compression and the technique of reversible data hiding in real cloud storage. Hence we have utilized the Discrete Wavelet Transform (DWT) algorithm.